Linking Technology Capabilities to Marketing Requirements: Case of Indonesian Aircraft Industry - Suharto, Yulianto (School of Business and Management Institut Teknologi Bandung, 2014)
Abstract. The relationship between strategic technology planning and the overall business strategy has been one of the growing fields that attract much interest both from academics and industrials point of view. The increasingly important role that technology plays in today’s business success is well established.Strategic technology planning activities–within a corporate level–are often implemented by applying integrated planning instrument, which allow firms to consider both technology-oriented and product-oriented aspects. This paper is an attempt to explore the role of strategic planning in the high tech industry using a specific case of aerospace industry in Indonesia. In order to compete effectively inthe open global marketplace, the company must learn to integrate technology managementwith strategic planning. In other words, all top managers have to linktheir technology capabilities to marketing requirements.Keywords: technology planning; business strategy; technology capability; marketing requirement; strategic mix